Kontrol Diri Santri dan Kepatuhan Terhadap Aturan di Pondok Pesantren - Riah Pratiwi (Universitas Mathla'ul Anwar Banten, 2026)
This study examines the relationship between self-control and student compliance with rules in Islamic boarding schools within a structured educational environment that emphasizes discipline and religious values. Using a Systematic Literature Review (SLR) approach, this study analyzed 15 empirical articles published between 2020 and 2025, sourced from national accredited journals and reputable international publications. The analysis was conducted through data reduction, categorization, and synthesis, guided by self-regulation theory and social learning perspectives. The findings indicate that students’ self-control generally falls within moderate to high levels and plays an important role in shaping compliant behavior. However, the relationship between self-control and compliance is not always linear, as compliance is also influenced by external factors such as supervision quality, peer dynamics, seniority culture, and consistency in rule enforcement. In several contexts, compliance emerges as a response to structural control rather than internalized self-regulation. These findings suggest that fostering sustainable student compliance requires an integrated approach that combines the development of individual self-control with the creation of a supportive institutional ecosystem. This study contributes to Islamic educational psychology by clarifying the conditional role of self-control in shaping authentic and enduring compliance among boarding school students.